Advances in computer games : 14th international conference, ACG 2015 Leiden, The Netherlands, July 1-3, 2015 revised selected papers (Lecture Notes in Computer Science / editors Gerhard Goos, Juris Hartmanis, and Jan van Leeuwen ;, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 14th International Conference on Advances in Computer Games, ACG 2015, held in Leiden, The Netherlands, in July 2015. The 22 revised full papers presented were carefully reviewed and selected from 34 submissions. The papers cover a wide range of topics such as Monte-Carlo Tree Search and its enhancements; theoretical aspects and complexity; analysis of game characteristics; search algorithms; and machine learning.